Probing the possibility of lesion formation/progression in vicinity of a primary atherosclerotic plaque: A fluid–solid interaction study and angiographic evidences. (5th May 2022) - Nooraeen, Ahmad; Ghalichi, Farzan; Taghizadeh, Hadi; Guidoin, Robert
Abstract: It is shown that certain locations in the arterial tree, such as coronary and cerebral arteries, are more prevalent to plaque formation. Endothelial activation and consequent plaque development are attributed to local hemodynamic parameters such as wall shear stress (WSS), oscillatory shear index (OSI), relative residence time (RRT), and stress phase angle. After a certain level of plaque progression, these hemodynamic parameters are disturbed before and after the plaque. In the current study, it is hypothesized that the vicinity of a primary lesion is susceptible for further degeneration and second plaque formation. A fluid–solid interaction (FSI) model of the coronary artery with different levels of asymmetric constriction, is simulated and the trend of hemodynamic parameters were studied in both of the plaque side (PS) and the opposite wall (facing the plaque [PF]). Also, a novel factor is introduced that can identify the high‐risk regions associated with WSS oscillations to negative values. Our results indicate that when more than half of the artery is constricted, the downstream of the plaque is highly exposed to endothelial pathogenesis the PS, such that negative WSS, and as well, critical values of OSI and RRT, that is, −1.2 Pa, 0.42 and 6.5 s, respectively arise in this region. PS endothelial cells in this region exposed to the highest risk of atherosclerosis based on the proposed index (3 out of 3). As well, three cases of angiographic images are provided that confirms existence of secondary lesion close to the primary one as predicted by our computational simulations. Abstract : In our study, the vicinity of a primary lesion is probed for further degeneration and formation of secondary plaques. The trend of hemodynamic parameters were studied on a fluid solid interaction model of the coronary artery wth different levels of asymmetric constrictions. Among the studied six regions, the plaque downstream demonstrated highest risk of further endothelial degeneration. Proposed resultswere confirmed by the angiographic evidences.